IMPLICATURE IN FACEBOOK CONVERSATION: PRAGMATIC ANALYSIS - Ika Susanti; Wiwik Mardiana (English Language Teaching Prima Journal (ELT), 2023)
Facebook is one of famous social network around people in Indonesia. Here, they can connect to a lot of person around the world. This paper focused in discussing the implicature meaning on speaker utterance and the aim of producing those utterance. Implicature from Yule were used to convey this problem. This paper used qualitative as the method to elaborate the analysis and discussion of the problem. The result of analysis show that speaker imply some point in their communication, such as unknown, agreement or disagreement, and yes/no. Furthermore, this paper conclude there are three aim of people in using implicature meaning while they are speaking; for saving act, making a joke, and mocking.